Profil Kemampuan Metakognisi Siswa dalam Memecahkan Masalah Kontekstual Matematika Ditinjau dari Gaya Belajar - Putri Lailiyah; Muhammad Saifuddin Zuhri; Dhian Endahwuri (Perkumpulan Kualitama Edukatika Indonesia, 2023)
Students' metacognitive abilities in solving mathematical contextual problems are quite low, one of the reasons is the differences in students' learning styles. This study aims to describe students' metacognitive abilities in solving mathematical contextual problems in terms of visual learning styles, auditory learning styles, and kinesthetic learning styles. This type of research is a descriptive qualitative research. This research was conducted at SMP N 34 Semarang in 2023/2024. The subjects of this study were students in class VIII G consisting of 1 student with a visual learning style, 1 student with an auditory learning style, and 1 student with a kinesthetic learning style. The data collection method used is a learning style questionnaire, metacognition ability tests, and interviews. While the triangulation used in this study is time triangulation. The results of this study indicate that 1 student with a visual learning style is able to master 1 of the 3 indicators of cognitive ability and tends to have low metacognition ability. Students with an auditory learning style are able to fulfill 3 of the 3 indicators of metacognitive ability and tend to have high metacognitive abilities. Students with a kinesthetic learning style are able to fulfill 2 of the 3 indicators of metacognitive ability and tend to have moderate metacognitive abilities. Based on the results of the analysis, it can be seen that students' metacognitive abilities in solving mathematical contextual problems with the subject of auditory and kinesthetic learning styles are higher than the subject of visual learning styles.